2013
DOI: 10.1016/j.jcot.2013.01.003
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of unicondylar medial Hoffa fracture associated with ipsilateral vertical patella fracture

Abstract: An 18 year old male patient was hit by a car to his motorcycle causing a unicondylar Hoffa fracture and an ipsilateral patella fracture. Hoffa fracture is a rare lesion and this association of injury has not been reported before.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…Bali et al described a case of tibia spine avulsion and quadriceps tendon rupture and was treated with non-absorbable suture material [9]. A patella fracture with associated Hoffa's fracture is treated with tension band wiring [10][11][12][13]. Shetty et al described a case of patellar tendon incarceration in Hoffa's fracture with an associated patellar fracture [10].…”
Section: Resultsmentioning
confidence: 99%
“…Bali et al described a case of tibia spine avulsion and quadriceps tendon rupture and was treated with non-absorbable suture material [9]. A patella fracture with associated Hoffa's fracture is treated with tension band wiring [10][11][12][13]. Shetty et al described a case of patellar tendon incarceration in Hoffa's fracture with an associated patellar fracture [10].…”
Section: Resultsmentioning
confidence: 99%
“…Ercin et al [67] Medial Two to 4 6.5 mm cancellous cannulated screws AP Symmetrical Case series Sasidharan et al [94] Medial Two 4 mm partially threaded cannulated cancellous screws AP Medial parapatellar arthrotomy CASE reportreconstructive osteotomy Calderazzi et al [95] Medial Four headless de 3,5 mm PA Medial (not specified) Case report Marzouki et al [96] Medial Two 6.5 cannulated screws AP Medial Case report Singh et al [76] Medial At least 2 6.5 cannulated screws AP Para-patellar approach Case series Mootha et al [97] Medial 3.0 mm × 4.0 mm cannulated partially threaded cancellous screws AP Medial parapatellar Case report Nandy et al [98] Medial Two 6.5 mm partially threaded cannulated cancellous screws and a 6 hole 3.5 mm recon plate AP and PL Medial subvastus Case report Biau et al [99] Lateral Three Herbert Screws AP Not reported Case report Kapoor et al [100] Medial type II -C* Two nonparallel headless Herbert screws PA Posterior Case report Say et al [101] Medial Two cannulated screws AP Arthroscopy-assisted reduction…”
Section: Case Seriesmentioning
confidence: 99%
“…In these cases, the associated patellar fracture results from a combination of forces: direct trauma causing the Hoffa fracture and possible indirect injuries from sudden contraction of the quadriceps muscle causing a vertical patellar fracture. [23]…”
Section: Injury Mechanismmentioning
confidence: 99%